RUSSIA’S FOREIGN POLICY TOWARD THE CAUCASUS UNDER VLADIMIR PUTIN - FARAJIRAD, Abdolreza; KHEZERZADE, Asaad (CENTRAL ASIA AND THE CAUCASUS, 2010)
This paper seeks to examine Russia’s foreign policy toward the Caucasus during Vladimir Putin’s presidency. Moreover, the period between 2000 and 2008 was one of the most important eras for Russian-Caucasian relations under Vladimir Putin in Russia, since his presidency brought about significant changes in Russia’s foreign policy. However, this study will not analyze pre-2000; instead, it will concentrate on certain facts and events that are important for understanding the period between 2000 and 2008. When examining states’ foreign policy, a number of different variables should be included in the analysis, and this makes it difficult to explain the foreign policy of one state in particular. Below we have tried to explore Russia’s foreign policy and foreign aims by means of psychological and other non-material factors.Each foreign policy is derived from the states and people’s normative system, which is primarily presented in the state constitution or other official documents, or even in states’ history presentations. In Russia’s case, these values are strictly linked to Russian history, when Russia was a great nation that decided all world affairs and Russians interpreted the position of the Russian state from this perspective.Russia’s instability after the collapse of the Soviet Union in the 1990s created great turmoil in Russia’s foreign policy. This was because the Russian political elites were unable to form a clear national identity or define the state’s national interests. They were unable to answer the old/new question of whether Russia belongs to the West or to the East.The first group of Russian political elites under Yeltsin (Westernizers) chose a pro-Western foreign policy and defined Russia’s national identity as a Western country. According to this definition, Russia tried to build good relations with the Western countries, especially the U.S, and forget the Cold War. The other wing was strongly against this view, they (Eurasianists) claimed that Russia was, is, and will always be Eurasian and a superpower. Putin belonged to the latter group that tried to restore Russia’s Great Power status.Putin shifted Russia’s foreign policy to a strong and certain one aimed at gaining maximum economic benefits. As Freedman says, Putin’s foreign policy was aimed at strengthening the Russian economy in the hope that in the not-too-distant future Russia might regain its status as a great power.1 Putin brought political and economic stability to Russia with his new foreign and domestic policy. So many Russians began referring to Putin as the New Russian Czar.